Exploring Green Banking Performance of Islamic Banks in Indonesia - Widiyanti, Dwi Retno; Hanifah, Sarah Hana; Supriani, Indri (Universitas Muhammadiyah Yogyakarta, 2025)
The sustainable movement in the financial sector, known as green banking, has emerged as a global standard that obligates the financial industry to adhere to social and environmental responsibilities. Indonesian Islamic banks' green banking initiatives are examined in this study. Green Banking Disclosure Index (GBDI) indicators for 13 Islamic commercial banks were collected from their five-year sustainability reports. Bose et al. (2018)'s 21 GDBI indicators were thoroughly analyzed. Jeucken's typology measurement showed banks' four-stage movement from defensive and preventative to aggressive and